Pengelolaan Digital Public Relations pada Media Sosial Instagram @halobandung - Shahra, Asmahan Nur; Safei, Agus Ahmad; Cholidah, Lida Imelda (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This study aims to determine the management of digital PR in disseminating information through social media Instagram by referring to the model proposed by Regina Luttrell which includes four aspects, namely the stages of share, optimize, manage, engage. This study uses a qualitative approach and descriptive method and uses data collection techniques with an interview and observation process. The results of this study indicate that the Instagram social media management activities of the Bandung City Leadership Communication Protocol are in accordance with four aspects of The Circular Model of Some, namely the dissemination of information content, issue search, maintaining communication, verified on Instagram to reach the public target.